Global Financial Governance: a Perspective from the International Monetary Fund - Ryszard Wilczyński (Contemporary Economics)
An environment for the activities of the International Monetary Fund (the IMF) has fundamentally changed over the two recent decades. The strong development of financial innovations as well as of financial globalisation was among major forces driving the change and shaping the economic growth worldwide. As some economies were able - with the support from financial markets – to accelerate their growth, other countries suffered from turbulences, which were reinforced and transferred internationally through the volatile financial markets. The process of international financial contagion makes the case for global financial governance, which so far has been left behind the development of markets. The IMF is mandated to play a central role in the global governance designed to ensure financial stability. The article reconsiders the Fund’s role and includes an overview and assessment of its activities, particularly in the context of the global financial crisis in 2007-2010. In the aftermath of this crisis, the international financial stability may, however, again be at risk as several external imbalances in the global economy may be hardly sustainable. It is argued in the paper that, in addition to a gradually improving surveillance and lending as well as to adjusting resources by the Fund, an enhanced credibility of the institution is needed so that its role in the process of the stabilising global financial system is strong and effective.